Liver Biopsy Crash Course - Andrew Arifin; David Driman; Jeremy Parfitt (Association of American Medical Colleges, 2016)
Abstract Introduction We recognized a need at our institution for a resource to facilitate self-learning of basic liver histology and pathology. An interactive, web-based learning module was determined to be an ideal type of educational tool. The Liver Biopsy Crash Course is a self-learning resource for mastering basic liver histology and pathology. It is a useful aid for hepatology clinical fellows participating in liver pathology biopsy rounds and preparing for their exams. It is also useful for off-service/clinical residents rotating through pathology and for junior-level pathology residents. Methods The module includes an instructor's guide, the web-based crash course resource, and a quiz. Results We are beginning to implement the use of the Liver Biopsy Crash Course with hepatology clinical fellows participating in liver pathology biopsy rounds and with junior-level pathology residents going through their initial liver pathology rotations. After completion of the module, residents were surveyed and asked about the impact on their understanding of liver pathology and if they felt that the resource was of benefit to their training. Any additional feedback was also invited. The results from this pilot have been overwhelmingly positive. Samples of actual comments received are: "I wish I had these a couple years ago... I wish there were more such modules on other topics;" "... quite a good review of liver pathology and helped establish a good approach to separating the different entities. I found it very useful (and enjoyable) to work through;" and "... very helpful, especially for junior residents who (like myself) may not be very familiar or confident with looking at the liver." Discussion We plan to further assess the effectiveness of the module in a second phase, which will involve assessing the learning impact on gastroenterology/hepatology fellows and off-service residents participating in liver biopsy rounds.